“MENYAMA BRAYA”: THE ROOTS OF RELIGIOUS MODERATION IN SINGARAJA BALI - Lestawi, I Nengah; I Made Wirahadi Kusuma (Anubhava: Jurnal Ilmu Komunikasi HIndu, 2023)
"Menyama Braya" is the local wisdom of the Balinese people, which has been carried out since ancient times from generation to generation. By carrying out the menyama braya tradition, religious moderation will be realized, strengthening integrity and solidarity among religious believers in the present and future. However, recently the implementation of the rule of meyama braya has been almost forgotten; this is due to several factors, including the change in direct communication to indirect through digital media that can communicate remotely; the condition of covid 19 has also caused people not to be able to communicate directly between fellow religions and the lack of information about the importance of living together with braya. By tracing several research results and journals, until now, no one has brought up the tradition of mesama braya about religious moderation in Singaraja City. Therefore researchers feel the need and are interested in raising this issue for research. This study uses a qualitative descriptive method with qualitative data types, namely data in the form of descriptive words, and supported by quantitative data, namely data in the form of numbers, such as the population based on religion. Primary data sources came from several informants: the Board of FKUB of Buleleng Regency, the Board of Traditional Villages in Buleleng District, Pekaseh (kelian Subak), Academics, and other general public. While the secondary data is in the form of library sources relevant to the problems studied, namely the research results, journals, and several books related to this research. The theories used in studying and analyzing the data are the theory of multiculturalism, integrative constructivism, and social action theory. Based on the data analysis, it can be seen that the meyama braya tradition is the root of religious moderation, which is implemented in the forms of the ngejot, magibung, sekaa duka, religious activities, and subak organizations